2022
DOI: 10.1186/s13046-022-02363-9
|View full text |Cite
|
Sign up to set email alerts
|

CDC20 in and out of mitosis: a prognostic factor and therapeutic target in hematological malignancies

Abstract: Cell division cycle 20 homologue (CDC20) is a well-known regulator of cell cycle, as it controls the correct segregation of chromosomes during mitosis. Many studies have focused on the biological role of CDC20 in cancer development, as alterations of its functionality have been linked to genomic instability and evidence demonstrated that high CDC20 expression levels are associated with poor overall survival in solid cancers. More recently, novel CDC20 functions have been demonstrated or suggested, including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 163 publications
(186 reference statements)
2
31
0
Order By: Relevance
“…Like TERT, CDC20 performs a variety of canonical and non-canonical functions, many of which can be implicated in cancer formation 49,52,58,59,[65][66][67][68][69][70][71] . Most crucial is its role in the cell cycle, where it interacts with the anaphase-promoting complex to degrade cyclin B and signal the end of metaphase and the start of anaphase 72 .…”
Section: Discussionmentioning
confidence: 99%
“…Like TERT, CDC20 performs a variety of canonical and non-canonical functions, many of which can be implicated in cancer formation 49,52,58,59,[65][66][67][68][69][70][71] . Most crucial is its role in the cell cycle, where it interacts with the anaphase-promoting complex to degrade cyclin B and signal the end of metaphase and the start of anaphase 72 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study demonstrated that E2F1-mediated transcription is essential for sphingosine-1-phosphate (S1P)-induced upregulation of PD-L1 expression ( 42 ), which may partly explain why FRGPI-high patients responded better to anti-PD-L1 than FRGPI-low patients in our study. Cell division cycle 20 (CDC20) acts as an anaphase-promoting complex activator that controls the proper segregation of chromosomes in mitosis ( 43 ). It was previously incorporated into several ferroptosis-related prognostic models in various tumors ( 44 , 45 ), but its specific functional role in ferroptosis has not been characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin B1 (CCNB1) is a crucial mitosis initiator and controller ( 48 ). CDC20 is a well-known regulator of cell division, regulating chromosome segregation during mitosis ( 49 ). The mitotic chromosome condensation is established by topoisomerase IIα (TOP2A), a core component of mitotic chromosomes ( 50 ).…”
Section: Discussionmentioning
confidence: 99%